Schaum's outline of theory and problems of operations research - Bronson, Richard (New York : McGraw-Hill, 1982)
This volume examines the concept of operations research which is concerned with the efficient allocation of scarce resources. This is done in well defined mathematical models of given situations.
Includes index.
lje 25/1/19
Loans
Keywords: Operations research; Resaerch